Regulating Enterprise Entry and Operations in Bihar : Towards Improved Implementation - World Bank (Washington, DC, 2013)
As part of its technical assistance initiative to develop (and strengthen) the regulatory framework for business, the single window system to stimulate the development of the private sector, the World Bank commissioned ICRA Management Consulting Services Limited (IMaCS) to conduct a detailed review and assessment of the investment and operating requirements in Bihar to understand its impact on implementation of the single window system and in turn to improve the overall investment climate in the state. This is particularly important as only 11 proposal of over a 1311 proposals received by the nodal State Investment Promotion Board (SIPB) have managed to reach the operational stage of business. The study was conducted in three phases: (i) Detailed mapping of the regulatory process for business entry at the pre-entry/post-entry stage for business entry in Bihar; (ii) Assessment of each license, clearance and inspection across parameters such as necessity, legality, efficiency and scope for simplification; and (iii) Suggestions on which licenses/ clearances/inspections should be retained, which could be abolished. This study was essentially based on primary research (multiple meetings with all concerned departments at both the central and state-level and with a cross-section of investors) as some new areas had to be addressed, particularly in the context of Bihar. Some of the key departments met include: Industries Department, Udyog Mitra, Bihar State Pollution Control Board, Bihar State Industries Development Corporation, Bihar Industrial Area Development Authority. Further, a number of stakeholders including private investors and state level industry associations were also consulted.